Concerning Beards Facial Hair, Health and Practice in England 1650-1900 - Withey, Alun (Facialities: Interdisciplinary Approaches to the Human Face, 2021)
This Open Access book provides a new understanding of the meanings and motivations behind the wearing of beards, moustaches and whiskers, and their associated practices and practitioners. Concerning Beards offers an important new long-term perspective on health and the male body in British society. It argues that the male face has long been an important site for the articulation of bodily health and vigour, as well as masculinity. Through an exploration of the history of male facial hair in England, Alun Withey underscores its complex meanings, medical implications and socio-cultural significance from the mid-17th to the early 20th century. Herein, he charts the gradual shift in concepts of facial hair and shaving - away from 'formal' medicine and practice - towards new concepts of hygiene and personal grooming. The ebook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com. Open access was funded by the Wellcome Trust. This book is part of the Facialities series, which explores the social, cultural and political significance of the face in human history.